Effect of storage at 37°C on allergenic potency of dried BCG vaccine - Obayashi, Yoji (1957)
Experiments were carried out to determine the effect of storage at 37°C on the allergenic potency for humans of dried BCG vaccine. From four lots of liquid vaccine, eight kinds of dried vaccine were prepared, four with 1% sodium glutamate and four with 1% sucrose as adjuvant. The eight vaccines were stored at 5°C and at 37°C for periods ranging from 1 month to 9 months, and were then used for the inoculation of primary-school children in Tokyo. These children were tuberculin-tested 1, 3 or 4 and, in a few cases, 12 months after vaccination, and the reactions were read approximately 48 hours after the tuberculin injection had been given. The tuberculin reactions induced by inoculation of the glutamate vaccines stored at 37°C were, in all cases, appreciably stronger than those induced by the sucrose vaccines after storage at the same temperature for the same period. A slight decrease in the potency of the glutamate vaccines was observed after storage for 3 months at 37°C, but storage for 1 month at this temperature did not appear to have any adverse effect on the potency.